Evaluation of fodder crops under Ailanthus excalsa Roxb. based agroforestry system - Ravi, R.; Divya, M.P.; Ratha Krishnan, P. (Indian Journal of Agroforestry, 2020)
Investigations were carried out with four shade tolerant fodder crops to identify the combatable one well suited for Ailanthus exce/sa based agroforestry system at Forest College and Research Institute, Mettupalayam. It revealed that the growth and yield of the test crops were reduced under intercropping when compare to pure cropping. Among the test crops, Desmanthus was most affected and fodder cowpea was the least affected. So fodder cowpea is identified as a combatable shade tolerant fodder and more suited for Ailanthus based agroforestry system.